Prospects of Trade Management System (TMS) in Nepalese Stock Market: Evidence from Structural Equation Modelling - Mahat, Pushpa; Devkota, Niranjan; Dhakal, Krishna; Mahato, Surendra; Paudel, Udaya Raj (Economic Journal of Development Issues, 2022)
This paper attempts to get opinions from the TMS users about its performance along with its main barriers in Nepalese stock market. Signaling theory and explanatory research design are adopted to seek causal relationship amongst online stock traders in Kathmandu valley. Following convenient sampling technique, 316 TMS users were interviewed with structured questionnaire; where data collection is done by using Kobo Toolbox. Structural Equation Modelling (SEM) is used to see the prospects of Trade Management System amongst TMS users using SPSS and SPSS AMOS software. Findings indicate that volume signals and online trading are significant causal relationship to investment behavior of TMS users in Kathmandu Valley which support Signaling Theory. Therefore, online trading would emerge as a more reliable investment platform and will provide large-scale investment possibilities in Nepalese stock market.